Networks in implementing policies. case study: Implementation of the Child Friendly Regency policy in East Luwu Regency - Al Jamily, Ismail; Haning, Moch.Thahir; Nur Indar, Nur Indrayati (Trigin Publisher, 2024)
This research aims to determine and analyze networks in policy implementation in a case study of child-friendly district policies in East Luwu. This type of research uses a descriptive qualitative approach. Data collection in this research was through observation and literature study. Data analysis includes data reduction, data presentation, and data interpretation, data conclusion and verification. The research results show that the implementation of child-friendly district policies was carried out with various efforts, including the issuance of regent regulations, the formation of a task force, and the formation of the Association of Indonesian Children's Friends Companies (APSAI). However, in its implementation, various problems and cases of violence against children were found to increase, so in-depth cooperation was needed.